The effect of a proposed device on developing the muscles of arms trunk to perform the serve from above in volleyball for third stage students - Zwayen, Jinan Naji; Farhood , Nidaa Yasir (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the research is to design and manufacture a mechanical device that contributes to the development of the muscles of the arms and torso, as they represent the most influential aspect of working in a volleyball game as well as developing the transmission skill from the top, and that their development achieves excellence and achievement in performance, this skill required physical and motor capabilities that depend on the investment of the nervous system The central and periphery determining the player’s movement within the field of play where the device contributed to developing these capabilities through its ability to work on it and the nature of the work of each part of its parts and as shown in its details in the body of this research, the two researchers used the experimental curriculum and the research sample consisted of (11 students) from Baghdad University, College of Physical Education and Sports Science, and the proposed training program (physical and skill) has been applied according to the specific curriculum and exercises chosen by the experts and specialists in the field of (training, volleyball, biomechanics, and tests). After completing the curriculum, the researcher extracted the results and Statistically processed according to the statistical bag (SPSS) and several conclusions were reached, including: The use of exercises that were prepared and performed on The device designed and proposed by the researcher led to an evolution in the level of physical and skill performance (the variables discussed) among the research sample under study.